Mapping the Potential Economy in The Old Town of Semarang to Support Its Sustainability - Kurniawati, Wakhidah; Kurniati, Rina; Soetomo, Sugiono; Rahmat, R. Rafii Bisatya; Firdaus, Annisa Sahira (Jurnal Teknik Sipil dan Perencanaan, 2020)
Abstract: The old town of Semarang is one of the most historical places in Semarang city, Indonesia, and in the 19th century, it was considered as a major business center. Currently, intending to revitalize this old town as the center for economy, the government has made it a central socio-cultural economic area for tourism development. This study aims to identify the potential economic spots in this old town to support its sustainability. The methodology used was cultural mapping with the geographic information system (ArcGIS) and direct observation in the old town. The results show that the core economic area is located on the main road. Meanwhile, the secondary economic area is situated behind the main roads. Both are selected because the original characteristic buildings which attract visitors. Therefore, adaptive reuse in an iconic building is one of the keys to economic sustainability in this old town.